Knowledge and attitudes of mothers of children with severe Pneumonia on oxygen therapy at Lilongwe Central Hospital. - Chabwera, Christina (Kamuzu University of Health Sciences, 2022)
Many studies have been done on Pneumonia and Oxygen therapy but none has been done on peoples' knowledge and attitudes towards Oxygen therapy. There is a tendency by most Malawian mothers of refusing Oxygen administration on their children because of past experience of seeing patients dying soon after Oxygen administration and because of other misconceptions they have on Oxygen therapy. This study will be done to find out the knowledge and attitudes of these mothers regarding Oxygen therapy. The aim is to remove the unnecessary misconceptions, which the mothers in Lilongwe District have in relation to Oxygen therapy so that total effective health care should be given to the children. The findings of the study will also help nurses at Lilongwe Central Hospital Paediatric Ward on how to provide accurate information to mothers regarding Oxygen therapy for them to understand its importance. A descriptive survey design will be used to anålyse the data. Using an interview guide, ten mothers will be interviewed (those with children with severe pneumonia and are to be or are on Oxygen therapy) for a period of four weeks. Data will be analysed using content analysis.